2019
DOI: 10.1007/s00146-019-00877-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of robotics and AI in technologically mediated human evolution: a constructive proposal

Abstract: This paper proposes that existing computational modeling research programs may be combined into platforms for the information of public policy. The main idea is that computational models at select levels of organization may be integrated in natural terms describing biological cognition, thereby normalizing a platform for predictive simulations able to account for both human and environmental costs associated with different action plans and institutional arrangements over short and long time spans while minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…An analysis of social issues based on some existing models of cognitive agents was proposed by White (in press). It was suggested that these models can help understand weighty social and political issues (such as those involved in international geopolitics), and they may lead to reasonable solutions of these consequential issues.…”
Section: Examples Of Cognitive Social Simulationmentioning
confidence: 99%
“…An analysis of social issues based on some existing models of cognitive agents was proposed by White (in press). It was suggested that these models can help understand weighty social and political issues (such as those involved in international geopolitics), and they may lead to reasonable solutions of these consequential issues.…”
Section: Examples Of Cognitive Social Simulationmentioning
confidence: 99%
“…To engineer this condition into artificial agents is one aim of research into artificial agency, and it may also be the best way to understand human morality and moral theory at the same time, with successes in these efforts anticipated in related fields, for example, in advancing work in computational modeling of social agency and of psychologically realistic sociopolitical structures in effective practical policy making (c.f. Naveh and Sun 2006;Sun 2013Sun , 2020White 2016White , 2020Han et al 2019Han et al , 2020Pereira and Saptawijaya 2015;Pereira 2019). Yet, it is unclear how to engineer moral autonomy into artificial agents, not to mention what to do if we do.…”
Section: Introductionmentioning
confidence: 99%